Water-controlled keto-enol tautomerization of a prebiotic nucleobase - Datar, Avdhoot; Paithankar, Harshad; Deb, Pranab; Chugh, Jeetender; Bagchi, Sayan; Mukherjee, Arnab; Hazra, Anirban (Journal of Physical Chemistry B, 2022)
Barbituric acid is believed to be a proto-RNA nucleobase that was used for biological information transfer on prebiotic earth before DNA and RNA in their present forms evolved. Nucleobases have various tautomeric forms and the relative stability of these forms is critical to their biological function. It has been shown that barbituric acid has a tri-keto form in the gas phase and an enol form in the solid state. However, its dominant tautomeric form in aqueous medium that is most relevant for biology has been investigated only to a limited extent and the findings are inconclusive. We have used multiple approaches, namely, molecular dynamics, quantum chemistry, NMR, and IR spectroscopy to determine the most stable tautomer of barbituric acid in solution. We find a delicate balance in the stability of the two tautomers, tri-keto and enol, which is tipped toward the enol as the extent of solvation by water increases.